Development of ECO-UHPC utilizing gold mine tailings as quartz sand alternative - Tanvir Ahmed; Mohamed Elchalakani; Hakan Basarir; Ali Karrech; Ehsan Sadrossadat; Bo Yang (Cleaner Engineering and Technology, 2021)
To ensure ultra-high performance, in terms strength and durability, coarse aggregate is typically avoided in UHPC (ultra-high performance concrete). Instead, very fine quartz sand is usually used as the only aggregate. However, excessive extraction of sand from natural resources and its grinding and refining processes to prepare very fine quartz-rich sand are not economically or environmentally lucrative. Limited number of studies sought to address this concern, and very few of these studies investigated the use of mine tailings (quartz based tailings and iron ore tailings) in UHPC as sand alternatives. In the present study, the possibility of utilizing gold mine tailings, sourced from a gold mine in Western Australia (WA), as conventional quartz sand substitute in UHPC has been investigated. Results suggest that UHPCs, made with up to 80% replacement of quartz sand by the tailings, exhibit compressive strengths comparable to or higher than that of the UHPC with 100% quartz sand. 28-day strength greater than 120 MPa is achievable up to 100% replacement. The water absorptions and the initial rate of absorptions of UHPCs with tailings are generally lower than those of the UHPC without tailings. The leachability of toxic metals from UHPC with up to 100% tailings content lies well below the regulatory thresholds. The combined material and transportation cost of UHPC can be reduced by up to 33.1% replacing quartz sand by the tailings, for construction near the mine site. The CO2 emission can be reduced by up to 12.1%. In the area near the mine site, utilization of the tailings can economically and environmentally, as well as in terms of durability, be a better option than quartz sand for construction works that require UHPC with 28-strength in excess of 120 MPa.